Relaxation processes in aqueous systems upon X-ray ionization: entanglement of electronic and nuclear dynamics - Slavíček, Petr; Kryzhevoi, Nikolai V. (The journal of physical chemistry letters, 2016)
The knowledge of primary processes following the interaction of high-energy radiation with molecules in liquid phase is rather limited. In the present Perspective, we report on a newly discovered type of relaxation process involving simultaneous autoionization and proton transfer between adjacent molecules, so-called proton transfer mediated charge separation (PTM-CS) process. Within PTM-CS, transients with a half-transferred proton are formed within a few femtoseconds after the core-level ionization event. Subsequent nonradiative decay of the highly nonequilibrium transients leads to a series of reactive species, which have not been considered in any high-energy radiation process in water. Nonlocal electronic decay processes are surprisingly accelerated upon proton dynamics. Such strong coupling of electronic and nuclear dynamics is a general phenomenon for hydrogen-bonded systems, however, its probability correlates strongly with hydration geometry. We suggest that the newly observed processes will impact future high-energy radiation-chemistry-relevant modeling, and we envision application of autoionization spectroscopy for identification of solution structure details.
Published: December 29, 2015
Gesehen am 08.05.2020